Human embryonic stem cells suffer from centrosomal amplification - Holubcová, Zuzana; Matula, Pavel; Sedláčková, Miroslava; Vinarský, Vladimír; Doležalová, Dáša; Bárta, Tomáš; Dvořák, Petr; Hampl, Aleš (Stem cells (Dayton, Ohio), 2011)
Propagation of human embryonic stem cells (hESCs) in culture tends to alter karyotype, potentially limiting the prospective use of these cells in patients. The chromosomal instability of some malignancies is considered to be driven, at least in part, by centrosomal overamplification, perturbing balanced chromosome segregation. Here, we report, for the first time, that very high percentage of cultured hESCs has supernumerary centrosomes during mitosis. Supernumerary centrosomes were strictly associated with an undifferentiated hESC state and progressively disappeared on prolonged propagation in culture. Improved attachment to culture substratum and inhibition of CDK2 and Aurora A (key regulators of centrosomal metabolism) diminished the frequency of multicentrosomal mitoses. Thus, both attenuated cell attachment and deregulation of machinery controlling centrosome number contribute to centrosomal overamplification in hESCs. Linking the excessive number of centrosomes in mitoses to the ploidy indicated that both overduplication within a single cell cycle and mitotic failure contributed to generation of numerical centrosomal abnormalities in hESCs. Collectively, our data indicate that supernumerary centrosomes are a significant risk factor for chromosome instability in cultured hESCs and should be evaluated when new culture conditions are being implemented.
Keywords: chromozomální nestabilita; Cell Line; protein-serin-threoninkinasy; Chromosomal Instability; Protein Serine-Threonine Kinases; buněčná diferenciace; Mitosis; centrozom; Cyclin-Dependent Kinase 2; Embryonic Stem Cells; embryonální kmenové buňky; cyklin-dependentní kinasa 2; aneuploidie; lidé; Aneuploidy; Humans; kinasy Aurora; buněčné linie; mitóza; Aurora Kinases; Centrosome; Cell Differentiation